(untitled) (Journal of actual problems of jurisprudence, 2019)
The author in article considers activity of IAB of RK under prevention, suppression , disclosing and investigation of crimes of terrorist character. Regulations and legal acts which is regulating activity of IAB are analysed, their basic purposes and problems are designated. Also the activity of internal affairs bodies is determined: on reception and using of the operative information on terrorist groups and the organizations; to definition by results of investigative activities, a site of terrorist groups; to the announcement of search of terrorists, deviating from investigation and court the persons preparing fulfilment of crimes of terrorist character and also in collecting and research of proofs. Key words: Crime of terrorist character, terrorism, extremism, terrorist groups and organizations, Internal Affairs bodies.